POSSIBILITIES FOR REGULATINGTHE STOCK MARKET IN UZBEKISTAN - Sultonov Sherali Nuralievich (Modern American Journals, 2025)
The article analyzes the essence, characteristics, scientific and theoretical issues of the stock market, as well as scientific views on the indicators of the Uzbek stock market. It formulates its own opinions, scientific and theoretical conclusions and proposals for further improving the activities of the Uzbek stock market.